The Effect of Shopee E-Commerce on Customer Satisfaction for Students of SMA Negeri 01 Class XI North Bengkulu - Dyah Noor Intan; Elvira Dewi Andini (Journal of Social Science and Humanities, 2023)
E-Commerce Shopee as an online shopping media platform that has offers that attract customers' attention. For that matter, one of them can be done through the media used to meet needs with Uses and Gratification Theory. The purpose of this study was to see the effect of Shopee E-Commerce on customer satisfaction among high school students. This research is a quantitative research presenting data in the form of descriptions by using information in the form of statistical numbers. With the technique of following data through primary data (questionnaire / questionnaire, observation) and secondary data (literature study, documentation). A questionnaire is a set of written questions for respondents to answer. Field observations. In fact, not all consumers are satisfied when online or using E-Commerce applications. Therefore, a problem arises that causes some people to be dissatisfied when using the Shopee E-Commerce application.